MELATIHKAN SELF EFFICACY SISWA KELAS X SMA NEGERI 1 SIDOARJO MELALUI PENERAPAN STRATEGI RECIPROCAL TEACHING PADA MATERI IKATAN KIMIA (UNESA Journal of Chemical Education, 2018)
This research aims to describe students’ self efficacy and student learning outcomes in the chemical bonding matter through the implementation of reciprocal teaching strategy. The research design which used was One Shot Case Study. The research was conducted on the grade X SMA Negeri 1 Sidoarjo. A research instrument that used consist of the observation sheet of learning implementation, students’ self efficacy questionnaire, and the posttest sheet as data on student learning outcomes. The data of learning implementation, students’ self efficacy and students learning outcomes were analyzed using quantitative analysis method. The results showed that (1) The average value of students’ self efficacy which obtained during three meetings are 73.21; 77.37; 84.72 with good and very good criteria. (2) The implementation of reciprocal teaching strategy obtained the percentage of three meetings respectively 92.50%; 93.75%; and 93.75% with good and very good criteria. (3) The learning outcomes of chemical bonding matter achieved by students obtained 100% classically. Keywords: reciprocal teaching strategy, student self efficacy, chemical bonding